Satisfaction and self-confidence among nursing students with simulation learning during COVID-19 - Mohammad Alsadi; Islam Oweidat; Huthaifah Khrais; Ahmad Tubaishat; Abdulqadir J. Nashwan (BMC, 2023)
Abstract Aim This survey aimed to investigate nursing students' satisfaction and self-confidence in simulation in education during the COVID-19 pandemic. Along with comparing these levels based on selected students' characteristics. Design A cross-sectional survey. Methods The survey was conducted at the faculty of nursing of a private university in Jordan. Students' satisfaction and self-confidence levels in simulation learning were measured using the National League for Nursing (NLN) Student Satisfaction and Self-confidence in Learning Scales. Results A total of 138 undergraduate nursing students participated in the survey. Students' satisfaction levels and self-confidence in simulation learning were lower (just above the scale's midpoint) than scores reported in similar surveys. The lowest student ratings were reported as "the variety of learning activities that can be done using simulation" and "the self-confidence to develop the needed skills and knowledge to be used in real clinical settings". The results also indicated that as students' progress in the bachelor's degree program, they develop higher levels of self-confidence in simulation-based learning. Conclusions Nursing students' experience of simulation learning was observed to be negatively affected by the COVID-19 pandemic. High-fidelity simulation, in particular, among other simulation modalities, can be more beneficial in similar situations. Education stakeholders are invited to invest in the resources of high-fidelity simulation to maximize its benefits and help in the recovery phase after the pandemic.